Application of modified equations of dynamics of average for operational forecasting of the turn and results of battle action - Borys Butvin; Olexander Mashkin; Olexii Solomitskii (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The article discusses the peculiarities of evaluation of quality of models and multimodel complexes of operations (combat actions). Such models are an effective and necessary tool for operational calculations at operational training activities, and procedures for assessing their qualitative properties are an important and responsible phase of the life cycle. In theoretical qualifiers the direct and reverse tasks of quality assessment are distinguished, the first is based on the direct quality measurement, the second is the quality management of the product to give it the necessary properties. The reverse task becomes especially relevant for multimodel complexes of operations (combat actions), which are initially built with a flexible structure, which includes the possibility of adding new models or modifying existing ones. Since the concept of quality includes both objective properties and subjective assessments of the utility of an object, which are evaluated by a single generic indicator with a qualifying method, it is natural to involve experts in the subject area in such assessments. The development of an expert information processing unit, together with modern software tools for data analysis and processing, provides an opportunity to organize the process of quality assessment of the most important properties of models and multimodel complexes. This is possible by establishing a non-linear analytical dependency that links independent variables (processed expert estimates) to a dependent variable, which is an integral quality assessment of models. The example of such a dependency with a high determinative factor of integrated quality assessment, as discussed in the article, confirmed the usefulness of such an approach. Having the described quality assessment tool will allow to calculate the integral quality indicator of selected model properties with a high accuracy, as well as can be used for qualifying analysis of possible modifications and structural changes in models and multimodel complexes of operations (combat actions).